The fraud portrait in budget planning by the regional government apparatus - Nova Indriani; Moh Nizarul Alim; Bambang Haryadi (Universitas Hayam Wuruk Perbanas, 2019)
This study aims to identify the existence of fraud that appears in the practice of budget preparation. It is a case study conducted in Blue Zone Regional Device by using participant observation method. The informants were the financial managers. The results showed that fraud on budgeting involves all parties ranging from planners, PPTKs, executive staff, and exchequer. Besides that, fraud on budgeting occurs in the form of commitments (fees), separation of funds for non-budgetary activities (pressure), the use of legal gaps that are less effective supervision system (opportunity) and assume reasonable what is done and all the Regional Tools do their jobs (rationalization)